The constitutional balance - Laws, John, 1945-2020 (Oxford, UK ; Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"The overall theme of the book is the relationship or tension between constitutional principles - fairness, reason and the presumption of liberty - and the democratic assembly's - the Parliament - right to vote the legislation of its choice. The point is important; it moulds our constitution and thus affects the way law is made and administered. The tension is generally eased by the deployment of statutory construction which brings these elements together in a coherent whole"--
The rule of law -- Democracy -- Two moralities -- The common law -- Reason, fairness, and the presumption of liberty -- Finding the edge : judicial deference -- Two mistakes : parliamentary intent and the ultra vires doctrine -- The sovereignty of parliament -- Human rights, free thought, and expression.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Constitutional law; Civil rights; Fairness; Liberty; Parliamentary practice; Constitutional & administrative law; Electronic books